Mapping the information landscape of the academic library - Whitworth, Andrew; Calvo, Maria-Carme Torras i; Moss, Bodil; Kifle, Nazareth Amlesom; Blåsternes, Terje (Qualitative and Quantitative Methods in Libraries, 2017)
This paper originates from a project entitled Bibliotek i Endring, or ―Changing Libraries‖, funded by the Norwegian National Library, which ran from June 2013 to March 2015. The project studied two academic libraries in Norway undergoing significant organisational changes: a merger of four campuses into one in one location, and a change of director in the other. Over this period of change, a variety of qualitative and quantitative methods were used to create maps of the information landscape (Lloyd 2010) in these two libraries.  The methodology provided summary data on the changing information landscapes for the project team, and also ‗on-the-spot‘ data for project participants. Group concept mapping sessions using the Ketso tool (www.ketso.com), held at regular intervals over the duration of the project, raised awareness in the librarians of issues like information sources, blockages, priorities, and necessary actions. Through giving the librarians a shared conceptual space in which to exchange information on tasks, values and actions, ―operational proximity‖ (Tagliaventi and Mattarelli 2006) came into being and boundaries between operational areas of the library could be crossed. The project illustrated how different groups could come together and make collective judgments about the relevance of informational resources in their landscape, a problem with which information science has long struggled (Saracevic 2007).